Thrombotic Thrombocytopenic Purpura Associated with Pazopanib - Umer Syed; Kramer J. Wahlberg; Daniel R. Douce; Julian R. Sprague (Case Reports in Hematology)
A 76-year-old male with metastatic renal carcinoma on day 24 of pazopanib was admitted with complaints of emesis, confusion, and hematuria. Laboratory testing showed acute kidney injury, hyperbilirubinemia, and thrombocytopenia. Scattered schistocytes were seen on peripheral smear, and he was diagnosed with thrombotic microangiopathy (TMA). He was started on daily, one-volume plasma exchange with rapid improvement in thrombocytopenia. ADAMTS13 activity returned as undetectably low with no inhibitor detected. After cessation of plasmapheresis, repeat ADAMTS13 activity returned as normal. Unfortunately, his platelet count started to downtrend within four days after developing septicemia thought to be due to a catheter-associated infection. He was placed on comfort care measures after discussion with his family. An autopsy listed the major cause of death as metastatic renal cell carcinoma. According to two separate systematic reviews, there have been no cases of proven drug-induced TMA where decreased ADAMTS13 activity was the identified mechanism. While pazopanib is also associated with TMA, this unique case suggests a novel potential mechanism for TMA associated with pazopanib and brings forth “drug-induced thrombotic thrombocytopenic purpura” that quickly responds to plasmapheresis as a possible new diagnostic entity requiring prompt recognition and treatment.